New patterns of abrasive wearproof of unalloyed steels and alloys - Дворук, В.І.; Бєлих, С.С. (Problems of Tribology, 2014)
Received new patterns of abrasive wearproof of steels and alloys, which can be summarized as proportionately "Wearproof (ε) – rheological parameter (R)". This allows us to consider the rheological parameters as a simple and adequatetest their durability.